2019
DOI: 10.1097/coh.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

The antibody response in HIV-1-infected donors

Abstract: Purpose of review-Although the goal of preventive HIV vaccine design is primarily the induction of broadly neutralizing antibodies (bNAbs), recent evidence suggests that a protective response will also benefit from Fc effector functions. Here, we provide an update on the antibody response to HIV infection, including both Fab and Fc-mediated antibody responses. We also highlight recent studies showing the interplay between these functions, focusing primarily on studies published in the last year.Recent findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The variable and constant regions of antibodies are often treated as two structurally and functionally distinct components, despite growing evidence of co-operation between them [18, 70]. We recently showed that early and potent Fc effector polyfunctionality predicted the development of neutralizing activity, highlighting that these different functions of antibodies are intrinsically linked [55].…”
Section: Discussionmentioning
confidence: 99%
“…The variable and constant regions of antibodies are often treated as two structurally and functionally distinct components, despite growing evidence of co-operation between them [18, 70]. We recently showed that early and potent Fc effector polyfunctionality predicted the development of neutralizing activity, highlighting that these different functions of antibodies are intrinsically linked [55].…”
Section: Discussionmentioning
confidence: 99%
“…4 ; Guo et al, 2019 ). Natural antibody development samples a heavily biased sequence space due to SHM targeting preferences, which impedes the natural development of effective antibodies against various diseases ( Julien and Wardemann, 2019 ; Murugan et al, 2020 ; Richardson and Moore, 2019 ; Schramm and Douek, 2018 ). Prior studies showed minimal correlation between SHM and immune protection for PfCSP-specific antibodies, and our findings support a hypothesis that natural antimalarial antibody development may be limited by incomplete sampling of rare mutations in vivo ( Schramm and Douek, 2018 ; Shen et al, 2020 ; Sheng et al, 2017 ; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). Rare mutations can play an important role in protective antibody development for infections with repeated antigen exposure like malaria and HIV-1 ( Julien and Wardemann, 2019 ; Murugan et al, 2020 ; Saunders et al, 2019 ; Shen et al, 2020 ) where chronic or repeated infection can sometimes enable the development of improbable mutations which achieve remarkable protective activity ( Richardson and Moore, 2019 ; Saunders et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%